Enviromental conditions and coordinate measuring machines accuracy - Vasić, Siniša; Stankov, Jelena (Journal of Production Engineering, 1989)
The accuracy of the Coordinate Measuring Machine (CMM) depends on the environmental and ambient conditions in which the measuring machine operates, including temperature, vibrations, air humidity, and dust. This paper provides a brief review of error causes, recommended microclimatic conditions, and developed methods for examining the accuracy of CMMs.